Dematerializing physical education in public schools: an indication of permanence - Cássia Maria Hess; Evando Carlos Moreira; Eliana de Toledo (Motriz: Revista de Educacao Fisica, 2018)
Abstract AIMS The objective of this study was to identify and analyze the most recurrent difficulties reported by Physical Education teachers of state and municipalized schools of the state of São Paulo, Brazil. METHODS The sample involved 13 cities (12 - Mogi-Mirim Region and 1 - São Paulo city), totaling 73 Physical Education teachers. Its research used a descriptive and exploratory methods and a questionnaire by instrument. The answers were analyzed using content analysis (Bardin, 2011). RESULTS As a result, the most reported difficulty, from both samples, was the lack, in quantity and in quality, of materials. Other difficulties were reported, like: inadequate physical space, indiscipline and demotivation of students. CONCLUSION We conclude that the material problem is a permanent difficulty in this discipline at school.